Development Of A Vibration Based Electromagnetic Energy Harvester (EEH) Using Graphene Silver Conductive Direct-Write Process For Automotive Thermal-Sensor - Ismail, Norhisham (2018)
Vibration Energy Harvesting is the concept of converting the kinetic energy inherent in vibrations to electricity. Vibration comes from many sources either natural vibration or forced vibration and vibration also can cause severe issue that may produce noise,impede stability and generate crack in structure.However,it can be beneficial in energy harvester as one of the power source which can be harvest and turn into electricity. With the development of low power energy harvester in recent years have given many opportunities to these sensors to functioning autonomously and wireless, especially in automotive.Furthermore, microelectromechanical systems (MEMS) concept has been on focus lately and become most important aspect in energy harvesting in micro-size device because the advantages of low-volume,low-weight and integration capability with other MEMS components.A double electromagnetic energy harvester (EEH) with three layer of conductive ink as coil was developed.The coil was made from graphene and silver conductive ink as a replacement of initial copper coil winding which limited for its bulky size and heavy weight.This research had study the conductivity of the conductive ink and development of the EEH’s device and system.EEH device also focused on its layers of the conductive ink coil and output power.The coil was printed on TPU or PET substrate due to their flexibility.Test was done on the conductive ink to find the most conductive material for the coil,which 40% loading composition of graphene and 80% laoding composition of silver gave most lower resistivity which resistivity,R is inversely proportional with current,I.Furthermore,damping test was done to measure damping coefficient of both conductive ink which graphene conductive ink’s damping coefficient is 0.01585 and for silver conductive ink is 0.00654.This damping coefficient will be used to obtain the output power of the EEH.Lastly,vibration experiment was done and from the experiment,EEH produce more power with more layers was printed but the power output was decreased with the increasing of the frequency.